PBT composite material and preparation method thereof

A PBT composite material with a balanced composition of flame retardants, reinforcing agents, and antioxidants, processed via twin-screw extrusion, addresses mechanical and flame retardancy issues, ensuring high performance and safety for new energy vehicle batteries.

CN119241996APending Publication Date: 2025-01-03DONGFENG MOTOR GRP
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411329656.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing PBT composite materials face challenges in achieving optimal mechanical properties, flame retardancy, and wear resistance, which are crucial for new energy vehicle battery components, as they are prone to combustion and heat-related issues.

Method used

A PBT composite material composed of specific ratios of PBT resin, halogen-free flame retardants (organic phosphorus and nitrogen-based), reinforcing agents, wear-resistant agents, antioxidants, and lubricants, processed through a twin-screw extrusion method to enhance mechanical properties and flame retardancy.

Benefits of technology

The composite material achieves high tensile strength, excellent flame retardancy, and wear resistance, with a glow-wire ignition temperature exceeding 700°C, while maintaining compatibility and processability, suitable for complex working environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241996A_ABST
    Figure CN119241996A_ABST
Patent Text Reader

Abstract

The invention provides a PBT composite material and a preparation method thereof, and belongs to the field of high polymer materials. Comprising 35-45 parts of PBT resin, 12-35 parts of a reinforcing agent, 10-35 parts of a halogen-free flame retardant, 1-5 parts of a wear-resistant agent, 0.1-1 part of an antioxidant and 0.2-3 parts of a lubricant, and the halogen-free flame retardant is composed of an organic phosphorus flame retardant and a nitrogen flame retardant. The composition of the raw materials of the PBT composite material is reasonably designed, and through compounding of the organic phosphorus flame retardant and the nitrogen flame retardant, an ideal flame retardant effect is obtained while a small amount of flame retardant is used; the lubricant and the antioxidant are used together, so that the dispersibility of other components such as the flame retardant and the reinforcing agent in the plastic can be improved. Therefore, the PBT composite material can obtain excellent wear resistance and mechanical properties, not only can realize extremely high glowing filament ignition temperature, but also has wear resistance and oxidation resistance. Further, the comprehensive performance of the PBT composite material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polymer materials, and in particular to a PBT composite material and a preparation method thereof. Background Art

[0002] PBT material is one of the five major engineering plastics. It has excellent mechanical properties and thermal stability, high temperature resistance, corrosion resistance and insulation performance. At present, new energy vehicle battery components are gradually changing from traditional metal products to thermal conductive plastics with advantages such as light weight, high plasticity, convenient molding and processing, and high production efficiency. PBT can be used to manufacture battery housings, connectors, seals, insulating gaskets, etc. For power battery systems, the performance of each component requires flame retardancy, dimensional stability, wear resistance, high strength, etc. Due to the shortcomings of plastics such as easy combustion, low heat deformation temperature, and low notch impact strength, there are safety hazards in practical applications. New energy electric vehicle batteries will generate heat during charging and discharging. If the heat cannot be dissipated in time, the temperature will continue to rise, and even cause thermal runaway of the battery, leading to accidents such as fire. Therefore, it is of great research significance to improve the wear resistance, flame retardancy and mechanical properties of PBT.

[0003] Most of the existing PBT composite materials are difficult to achieve the desired performance. Adding flame retardants will lead to a decrease in mechanical properties, while adding glass fiber will lead to a decrease in flame retardancy. At the same time, due to the complex working environment of the parts, the material is also required to have good wear resistance. Therefore, how to improve the comprehensive performance of PBT composite materials is a technical problem that needs to be solved urgently. Summary of the invention

[0004] The present application provides a PBT composite material and a preparation method thereof to solve the following technical problem: how to improve the comprehensive performance of the PBT composite material.

[0005] In the first aspect, the present application provides a PBT composite material, wherein the raw materials of the PBT composite material include, by weight: 35 to 45 parts of PBT resin, 12 to 35 parts of reinforcing agent, 10 to 35 parts of halogen-free flame retardant, 1 to 5 parts of wear-resistant agent, 0.1 to 1 part of antioxidant, and 0.2 to 3 parts of lubricant, wherein the halogen-free flame retardant is composed of an organic phosphorus flame retardant and a nitrogen-based flame retardant.

[0006] Optionally, the mass ratio of the organic phosphorus flame retardant to the nitrogen flame retardant is (8-25):(2-10).

[0007] Optionally, the halogen-free flame retardant includes: one or more of red phosphorus, aluminum hypophosphite, ammonium polyphosphate, diethyl aluminum hypophosphite, melamine, aminotrimethylene phosphonic acid aluminum, diethyl aluminum phosphate, melamine cyanurate, melamine phosphate, phenyl phosphate, siloxane and 2,6-diformyl-4-methoxyphenol.

[0008] Optionally, the reinforcing agent is short fibers, the size of the short fibers is 1 mm to 5 mm, and the short fibers include: one or more of carbon fibers, glass fibers and basalt fibers.

[0009] Optionally, the wear-resistant agent includes: one or more of carbon nanotubes, expandable graphite, graphene, graphene oxide and carbon fiber.

[0010] Optionally, the antioxidant includes: one or more of bis(4-octylphenol) diphosphate, tris(2,4-di-tert-butyl) phosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and phosphite antioxidants; and / or, the lubricant includes: ethylene bisstearamide.

[0011] Optionally, the PBT composite material meets at least one of the following properties: tensile strength of 90 MPa to 130 MPa, flame retardancy of 1.6 mm of V0, glow-wire ignition temperature of >700° C., and friction coefficient of 0.2 to 0.3.

[0012] In a second aspect, the present application provides a method for preparing the PBT composite material according to any one embodiment of the first aspect, the method comprising:

[0013] Adding an anti-wear agent, an antioxidant and a lubricant into a solvent, and then mixing them to obtain a mixed solution;

[0014] Adding halogen-free flame retardant to the mixed solution in batches, stirring and drying, and obtaining a flame retardant and wear-resistant agent;

[0015] The flame retardant and wear resistant agent, PBT resin and reinforcing agent are respectively added into three hoppers of a twin-screw extruder, and the material discharge flow rates of the three hoppers are controlled, followed by melt extrusion granulation and drying to obtain a PBT composite material.

[0016] Optionally, the temperature of the twin-screw extruder is 100° C. to 300° C., and the screw speed is 150 r / min to 250 r / min.

[0017] Optionally, the discharge flow rates of the three hoppers are 20kg / h to 30kg / h, 4kg / h to 10kg / h and 0.5kg / h to 5kg / h respectively.

[0018] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0019] The present application provides a PBT composite material, wherein the raw materials of the PBT composite material include, by weight: 35 to 45 parts of PBT resin, 12 to 35 parts of reinforcing agent, 10 to 35 parts of halogen-free flame retardant, 1 to 5 parts of wear-resistant agent, 0.1 to 1 part of antioxidant, and 0.2 to 3 parts of lubricant, wherein the halogen-free flame retardant is composed of organic phosphorus flame retardant and nitrogen flame retardant. The present application rationally designs the raw material composition of the raw materials of the PBT composite material, and obtains an ideal flame retardant effect while using less flame retardant by compounding organic phosphorus flame retardant and nitrogen flame retardant; by using lubricant and antioxidant together, the dispersibility of other components such as flame retardant and reinforcing agent in plastic can be improved. Thus, the PBT composite material can obtain excellent wear resistance and mechanical properties, and can not only achieve extremely high glow wire ignition temperature, but also take into account wear resistance and antioxidant properties. Thus, the comprehensive performance of the PBT composite material is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0021] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0022] Figure 1 A schematic flow chart of a method for preparing a PBT composite material provided in an embodiment of the present application. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0024] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0025] In addition, in the description of the specification of the present application, the terms "including", "comprising", etc. mean "including but not limited to". In this article, relational terms such as "first" and "second", etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A and B can be singular or plural. In this article, "at least one" means one or more, and "plurality" means two or more. "At least one", "the following at least one item (items)" or similar expressions refer to any combination of these items, including any combination of single items (items) or plural items (items). For example, "at least one of a, b, or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc or abc, where a, b, c can be single or plural, respectively.

[0026] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0027] The present application provides a PBT composite material, wherein the raw materials of the PBT composite material include, by weight: 35 to 45 parts of PBT resin, 12 to 35 parts of reinforcing agent, 10 to 35 parts of halogen-free flame retardant, 1 to 5 parts of wear-resistant agent, 0.1 to 1 part of antioxidant, and 0.2 to 3 parts of lubricant, wherein the halogen-free flame retardant is composed of an organic phosphorus flame retardant and a nitrogen-based flame retardant.

[0028] In some embodiments, the mass ratio of the organic phosphorus flame retardant to the nitrogen flame retardant is (8-25):(2-10).

[0029] The present application rationally designs the raw material composition of the raw materials of the PBT composite material, thereby improving the comprehensive performance of the PBT composite material. The specific reasons for the raw material composition are as follows:

[0030] (1) By adding halogen-free flame retardants and wear-resistant agents at the same time, when the wear-resistant agent is used in combination with the phosphorus-based flame retardant in the halogen-free flame retardant, the phosphorus element in the phosphorus-based flame retardant reacts with oxygen in the air at high temperatures to form non-combustible substances such as phosphoric acid or polyphosphoric acid. These substances will form a protective film on the surface of the wear-resistant agent to isolate oxygen and heat, thereby achieving a flame retardant effect. At the same time, the phosphorus-based flame retardant will produce a large amount of non-combustible gases such as ammonia and nitrogen during the decomposition process. These gases can dilute the oxygen concentration in the air and reduce the rate of the combustion reaction. In addition, the phosphorus-based flame retardant can also promote the carbonization reaction on the surface of the wear-resistant agent to form a dense carbon layer, further preventing oxygen and heat from transferring to the inside and improving the flame retardant performance. Thus.

[0031] (2) Through the compound use of organophosphorus flame retardants and nitrogen flame retardants, the flame retardant of organophosphorus flame retardants mainly works in the condensed phase, by forming phosphoric acid as a dehydrating agent, promoting carbonization, and reducing heat conduction from the flame to the condensed phase. At the same time, phosphoric acid can absorb heat, prevent CO from oxidizing to CO2, and reduce the heating process. In addition, it can also form a thin glassy or liquid protective layer in the condensed phase, reducing oxygen diffusion and heat and mass transfer between the gas phase and the solid phase; Nitrogen flame retardant: With nitrogen as the main active ingredient, when heated and burned, it can form a uniform carbon foam layer on the surface of the polymer, which plays a role in heat insulation and oxygen isolation. At the same time, nitrogen flame retardants will decompose and produce non-combustible gases (such as N2, NO2, NH3, NH2 and H2O, etc.), dilute the concentration of oxygen and combustible gases around the burning material, and take away most of the heat through decomposition and sublimation to reduce the surface temperature of the burning material. Phosphorus-nitrogen synergistic flame retardants (i.e., the compound use of organic phosphorus flame retardants and nitrogen flame retardants) will form intermediates containing NP bonds during the reaction process. This intermediate can improve the carbonyl reaction activity and phosphorylation rate, thereby increasing the carbonization rate. At the same time, nitrogen compounds can delay the volatilization loss of phosphorus-containing compounds in the condensed phase, strengthen the oxidation of phosphorus compounds, and release flame-retardant gases including ammonia and nitrogen. These gases can further dilute the combustible gas, slow down the spread of combustion, and promote the formation of a fluffy carbon layer. Phosphorus-nitrogen synergistic flame retardants combine acid sources, carbon sources, and gas sources in one body. They are thermally decomposed to form metaphosphoric acid or polymetaphosphoric acid. Acidic substances promote the dehydration of polymers to form carbon. At the same time, a glassy thin layer of polymetaphosphoric acid covers the surface of the residual carbon layer, inhibiting further oxidation of the carbon layer. Through synergistic action, phosphorus-nitrogen synergistic flame retardants can increase the mass of the residue while improving the anti-melting performance of the material, thereby significantly improving the flame retardant efficiency. In addition, both organic phosphorus flame retardants and nitrogen flame retardants meet the requirements of environmental protection and safety. Organic phosphorus flame retardants have the advantages of low smoke, non-toxicity, low halogen, and halogen-free, while nitrogen flame retardants have the characteristics of low toxicity, low smoke, and stability to heat and ultraviolet rays. Their combined use can further reduce the toxic gases and smoke generated during the combustion process and improve the environmental performance of the material. Therefore, organic phosphorus flame retardants and nitrogen flame retardants play a synergistic flame retardant effect, achieving ideal flame retardant effects while using less flame retardants and reducing costs.

[0032] (3) The added lubricant not only has a good external lubrication effect, but also has a good internal lubrication effect, which improves the fluidity and demoulding properties of the melt-insulated plastic during plastic molding processing, and makes the product have extremely high surface finish and smoothness. At the same time, the added lubricant and other antioxidants have a very significant synergistic effect, which can improve the dispersibility of other components such as flame retardants and reinforcing agents in plastics. Therefore, it can improve the mechanical and flame retardant properties of the composite material, improve the wear resistance and oxidation resistance of the material, and obtain long-term flame retardancy.

[0033] Therefore, the present application uses a specific ratio to make the material have high mechanical properties and wear resistance while obtaining ideal flame retardant properties, and can meet the needs of complex working environments. For example, the PBT resin can be 35 parts, 36 parts, 37 parts, 38 parts, 39 parts, 40 parts, 42 parts, 44 parts, 45 parts, etc., the reinforcing agent can be 12 parts, 15 parts, 18 parts, 20 parts, 25 parts, 30 parts, 35 parts, etc., the halogen-free flame retardant can be 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, etc., the wear agent can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, etc., the antioxidant can be 0.1 parts, 0.2 parts, 0.4 parts, 0.6 parts, 0.8 parts, 1 part, etc., the lubric ... The lubricant can be 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, etc.; the mass ratio of the organophosphorus flame retardant to the nitrogen flame retardant is organophosphorus flame retardant: nitrogen flame retardant = (8-25): (2-10), and the mass ratio of the organophosphorus flame retardant to the nitrogen flame retardant can be 8:2, 8:4, 8:6, 8:8, 8:10, 15:2, 15:4, 15:6, 15:8, 15:10, 25:2, 25:4, 25:6, 25:8, 25:10, etc.

[0034] In some embodiments, the PBT resin is prepared by polycondensation of 1,4-butanediol (BDO) (density: 1.0171 (20 / 4°C), appearance: colorless viscous oily liquid) and pure terephthalic acid (PTA) (appearance: white powdery crystals, density: 1.510 g / cm), and is prepared through a mixing process, and has an intrinsic viscosity of 1.0 dL / g to 1.20 dL / g.

[0035] In some embodiments, the halogen-free flame retardant includes one or more of red phosphorus, aluminum hypophosphite, ammonium polyphosphate, diethyl aluminum hypophosphite, melamine, aminotrimethylene phosphonic acid aluminum, diethyl aluminum phosphate, melamine cyanurate, melamine phosphate, phenyl phosphate, siloxane and 2,6-diformyl-4-methoxyphenol.

[0036] In some embodiments, the reinforcing agent is short fibers, the size of the short fibers is 1 mm to 5 mm, and the short fibers include: one or more of carbon fibers, glass fibers, and basalt fibers.

[0037] In some embodiments, the wear-resistant agent includes one or more of carbon nanotubes, expandable graphite, graphene, graphene oxide and carbon fiber.

[0038] In some embodiments, the antioxidant includes: one or more of bis(4-octylphenol) diphosphate, tris(2,4 di-tert-butyl) phosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and phosphite antioxidants; and / or, the lubricant includes: ethylene bisstearamide.

[0039] It should be noted that bis(4-octylphenol) diphosphate prevents the occurrence of free radical chain reactions by capturing and eliminating free radicals, thereby protecting the material from oxidation. Tris(2,4-di-tert-butyl) phosphite decomposes hydroperoxides to generate stable inactive products, thereby inhibiting the degradation process of the material and extending its service life. Pentaerythritol tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate terminates the free radical chain reaction by providing hydrogen atoms to form stable free radical products, thereby protecting the material from oxidation.

[0040] In some embodiments, the PBT composite material satisfies at least one of the following properties: a tensile strength of 90 MPa to 130 MPa, a flame retardant grade of V0 at 1.6 mm, a glow-wire ignition temperature of >700° C., and a friction coefficient of 0.2 to 0.3.

[0041] This application is based on the combination of specific flame retardants, antioxidants and lubricants, which can make the halogen-free flame retardant in the product not only exert flame retardant properties but also make the PBT composite material obtain excellent wear resistance and mechanical properties, which can not only achieve extremely high glow wire ignition temperature, but also take into account wear resistance and antioxidant properties. At the same time, the added lubricant significantly improves the compatibility of each component with the PBT matrix resin. The product has high impact resistance, high fluidity and strong processability.

[0042] The PBT composite material prepared in the present application can be used to prepare peripheral components of new energy vehicle batteries, such as BMS, BDU back covers, brackets, connectors, etc.

[0043] Figure 1 A schematic flow chart of a method for preparing a PBT composite material provided in an embodiment of the present application.

[0044] See also Figure 1 The present application provides a method for preparing the PBT composite material described in any one of the above embodiments, the method comprising:

[0045] S1, adding an anti-wear agent, an antioxidant and a lubricant to a solvent, and then mixing them to obtain a mixed solution;

[0046] In some embodiments, the solvent is anhydrous ethanol.

[0047] S2, adding halogen-free flame retardant to the mixed solution in batches, and then stirring and drying to obtain a flame retardant and wear-resistant agent;

[0048] The solvent is removed by drying to obtain uniformly mixed raw materials of flame retardant and wear resistant agent.

[0049] In some embodiments, the stirring time is 5 min.

[0050] Wear-resistant agents (such as carbon nanotubes) tend to agglomerate in solutions due to their nanoscale size and large specific surface area. Adding them to anhydrous ethanol and stirring them can effectively utilize ethanol as a dispersion medium, reduce the interaction between carbon nanotubes, and achieve a better dispersion state. The magnetic stirrer can provide uniform stirring force to ensure that the carbon nanotubes are evenly distributed in ethanol and avoid excessive or low local concentrations. At the same time, adding flame retardants in batches helps to control the distribution and concentration of flame retardants in the system and avoid excessive local concentrations caused by one-time addition, which affects the performance of the material. Gradual introduction can ensure that there is enough time for the flame retardant to interact with the carbon nanotubes and ethanol, which is conducive to forming a stable dispersion system. A continuous stirring time of 5 minutes can ensure that the components in the system are fully mixed, reduce local concentration differences, and improve dispersion uniformity. The magnetic stirrer can provide a stable stirring force to avoid performance differences caused by uneven stirring. Improve material performance: The composite material prepared by the above steps can improve the overall performance of the material, such as flame retardancy, mechanical strength, etc., due to the uniform dispersion of carbon nanotubes and flame retardants. At the same time, evenly dispersed carbon nanotubes can form a good conductive network in the material, improving the conductive properties of the material. In summary, adding carbon nanotubes to anhydrous ethanol and stirring evenly, adding flame retardants in batches, and using a magnetic stirrer to stir the dispersed system for 5 minutes can ensure the uniform dispersion of carbon nanotubes and flame retardants in the system and improve the overall performance of the material.

[0051] S3, adding the flame retardant and wear resistant agent, PBT resin and reinforcing agent into three hoppers of a twin-screw extruder respectively, and controlling the discharge flow of the three hoppers, and then performing melt extrusion granulation and drying to obtain a PBT composite material.

[0052] In some embodiments, the temperature of the twin-screw extruder is 100° C. to 300° C., and the screw speed is 150 r / min to 250 r / min.

[0053] In some embodiments, the discharge flow rates of the three hoppers are 20 kg / h to 30 kg / h, 4 kg / h to 10 kg / h, and 0.5 kg / h to 5 kg / h, respectively.

[0054] In some embodiments, the drying temperature is 100° C. to 120° C., and the drying time is 2 h to 6 h.

[0055] The product prepared by the preparation method of the PBT composite material is the above-mentioned PBT composite material. The chemical composition of the PBT composite material prepared by the preparation method of the PBT composite material can refer to the above-mentioned embodiment. Since the preparation method of the PBT composite material adopts part or all of the technical solutions of the PBT composite material embodiment, it at least has all the beneficial effects brought by the technical solutions of the PBT composite material embodiment, which will not be repeated here one by one.

[0056] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.

[0057] Example 1

[0058] This embodiment provides a PBT composite material, and the raw materials of the PBT composite material include, by weight: 45 parts of PBT resin, 25 parts of reinforcing agent, 12 parts of organic phosphorus flame retardant, 6 parts of nitrogen flame retardant, 1 part of wear-resistant agent, 1 part of antioxidant, and 3 parts of lubricant. Among them, the intrinsic viscosity of the PBT resin (PBT 1100) is 1.0 dL / g, the reinforcing agent is 3 mm carbon fiber (carbon fiber T300), the organic phosphorus flame retardant is diethyl aluminum hypophosphite (polyester flame retardant Exolit OP1260), the nitrogen flame retardant is MCA (melamine cyanurate, chemical formula: C6H9N9O3, CAS: 37640-57-6), the wear-resistant agent is carbon nanotube (carbon nanotube HW-C910L), the antioxidant is polyhedral hindered phenol antioxidant AT-10, and the lubricant is ethylene bis stearic acid amide (linear molecular formula: [CH3(CH2) 16 CONHCH2-]2, CAS number: 110-30-5, molecular weight: 593.02).

[0059] Based on the raw material composition of the above-mentioned PBT composite material, this embodiment also provides a method for preparing the PBT composite material, comprising the following steps:

[0060] S11, adding the anti-wear agent, antioxidant and lubricant to anhydrous ethanol, using a magnetic stirrer to disperse and stir for 5 minutes to obtain a uniformly mixed mixture;

[0061] S21, adding the organic phosphorus flame retardant and the nitrogen flame retardant to the mixed solution in batches, using a magnetic stirrer to disperse and stir for 5 minutes, and then putting it into a vacuum drying oven to remove ethanol to obtain a uniformly mixed flame retardant and wear-resistant agent;

[0062] S31. Add the flame retardant and wear resistant agent, PBT resin and reinforcing agent to the three hoppers of the twin-screw extruder respectively, and control the discharge flow rate of the three hoppers, and then carry out melt extrusion granulation. After extrusion granulation by the twin-screw extruder, dry at 110°C for 4 hours to obtain PBT composite particles, wherein the temperatures of the nine zones of the twin-screw extruder are set to 100°C, 255°C, 255°C, 255°C, 255°C, 255°C, 265°C, and 265°C, respectively, and the rotation speed is 190r / min, and the discharge flow rates of the three hoppers are set to 27.2kg / h, 4.8kg / h, and 1kg / h, respectively.

[0063] Example 2

[0064] This embodiment provides a PBT composite material, and the raw materials of the PBT composite material include, by weight: 45 parts of PBT resin, 15 parts of reinforcing agent, 6 parts of organic phosphorus flame retardant, 12 parts of nitrogen flame retardant, 1 part of anti-wear agent, 1 part of antioxidant, and 2 parts of lubricant. The specific types of raw materials are the same as those in Example 1.

[0065] Based on the raw material composition of the PBT composite material, this embodiment also provides a method for preparing the PBT composite material, comprising the following steps:

[0066] S11, adding the anti-wear agent, antioxidant and lubricant to anhydrous ethanol, using a magnetic stirrer to disperse and stir for 5 minutes to obtain a uniformly mixed mixture;

[0067] S21, adding the organic phosphorus flame retardant and the nitrogen flame retardant to the mixed solution in batches, using a magnetic stirrer to disperse and stir for 5 minutes, and then putting it into a vacuum drying oven to remove ethanol to obtain a uniformly mixed flame retardant and wear-resistant agent;

[0068] S31. Add the flame retardant and wear resistant agent, PBT resin and reinforcing agent into three hoppers of a twin-screw extruder respectively, and control the discharge flow of the three hoppers, and then perform melt extrusion granulation. After extrusion granulation by the twin-screw extruder, dry at 110°C for 4 hours to obtain PBT composite particles, wherein the parameter setting of the twin-screw extruder is the same as that in Example 1.

[0069] Example 3

[0070] This embodiment provides a PBT composite material, and the raw materials of the PBT composite material include, by weight: 45 parts of PBT resin, 30 parts of reinforcing agent, 9 parts of organic phosphorus flame retardant, 9 parts of nitrogen flame retardant, 1 part of wear resistance agent, 1 part of antioxidant, and 3 parts of lubricant. The specific types of raw materials are the same as those in Example 1.

[0071] Based on the raw material composition of the PBT composite material, this embodiment also provides a method for preparing the PBT composite material, comprising the following steps:

[0072] S11, adding the anti-wear agent, antioxidant and lubricant to anhydrous ethanol, using a magnetic stirrer to disperse and stir for 5 minutes to obtain a uniformly mixed mixture;

[0073] S21, adding the organic phosphorus flame retardant and the nitrogen flame retardant to the mixed solution in batches, using a magnetic stirrer to disperse and stir for 5 minutes, and then putting it into a vacuum drying oven to remove ethanol to obtain a uniformly mixed flame retardant and wear-resistant agent;

[0074] S31. Add the flame retardant and wear resistant agent, PBT resin and reinforcing agent into three hoppers of a twin-screw extruder respectively, and control the discharge flow of the three hoppers, and then perform melt extrusion granulation. After extrusion granulation by the twin-screw extruder, dry at 110°C for 4 hours to obtain PBT composite particles, wherein the parameter setting of the twin-screw extruder is the same as that in Example 1.

[0075] Comparative Example 1

[0076] This comparative example provides a PBT composite material, wherein the raw materials of the PBT composite material include, by weight: 45 parts of PBT resin, 15 parts of reinforcing agent, 12 parts of organic phosphorus flame retardant, 6 parts of nitrogen flame retardant, and 1 part of antioxidant. The specific types of the raw materials are the same as those in Example 1.

[0077] Based on the raw material composition of the above-mentioned PBT composite material, this comparative example also provides a method for preparing the PBT composite material, comprising the following steps:

[0078] S11, adding an antioxidant and a lubricant to anhydrous ethanol, and using a magnetic stirrer to disperse and stir for 5 minutes to obtain a uniformly mixed mixture;

[0079] S21, adding the organic phosphorus flame retardant and the nitrogen flame retardant to the mixed solution in batches, using a magnetic stirrer to disperse and stir for 5 minutes, and then putting it into a vacuum drying oven to remove ethanol to obtain a uniformly mixed flame retardant and wear-resistant agent;

[0080] S31. Add the flame retardant and wear resistant agent, PBT resin and reinforcing agent into three hoppers of a twin-screw extruder respectively, and control the discharge flow of the three hoppers, and then perform melt extrusion granulation. After extrusion granulation by the twin-screw extruder, dry at 110°C for 4 hours to obtain PBT composite particles, wherein the parameter setting of the twin-screw extruder is the same as that in Example 1.

[0081] Comparative Example 2

[0082] This comparative example provides a PBT composite material, wherein the raw materials of the PBT composite material include, by weight: 45 parts of PBT resin, 25 parts of reinforcing agent, 18 parts of nitrogen flame retardant, 1 part of anti-wear agent, 1 part of antioxidant, and 3 parts of lubricant. The specific types of the raw materials are the same as those in Example 1.

[0083] Based on the raw material composition of the above-mentioned PBT composite material, this comparative example also provides a method for preparing the PBT composite material, comprising the following steps:

[0084] S11, adding the anti-wear agent, antioxidant and lubricant to anhydrous ethanol, using a magnetic stirrer to disperse and stir for 5 minutes to obtain a uniformly mixed mixture;

[0085] S21, adding nitrogen flame retardant to the mixed solution in batches, using a magnetic stirrer to disperse and stir for 5 minutes, and then putting it into a vacuum drying oven to remove ethanol to obtain a uniformly mixed flame retardant and wear-resistant agent;

[0086] S31. Add the flame retardant and wear resistant agent, PBT resin and reinforcing agent into three hoppers of a twin-screw extruder respectively, and control the discharge flow of the three hoppers, and then perform melt extrusion granulation. After extrusion granulation by the twin-screw extruder, dry at 110°C for 4 hours to obtain PBT composite particles, wherein the parameter setting of the twin-screw extruder is the same as that in Example 1.

[0087] Comparative Example 3

[0088] This comparative example provides a PBT composite material, wherein the raw materials of the PBT composite material include, by weight: 45 parts of PBT resin, 25 parts of reinforcing agent, 18 parts of organic phosphorus flame retardant, 1 part of anti-wear agent, 1 part of antioxidant, and 3 parts of lubricant. The specific types of the raw materials are the same as those in Example 1.

[0089] Based on the raw material composition of the above-mentioned PBT composite material, this comparative example also provides a method for preparing the PBT composite material, comprising the following steps:

[0090] S11, adding the anti-wear agent, antioxidant and lubricant to anhydrous ethanol, using a magnetic stirrer to disperse and stir for 5 minutes to obtain a uniformly mixed mixture;

[0091] S21, adding the organophosphorus flame retardant to the mixed solution in batches, using a magnetic stirrer to disperse and stir for 5 minutes, and then putting it into a vacuum drying oven to remove ethanol to obtain a uniformly mixed flame retardant and wear-resistant agent;

[0092] S31. Add the flame retardant and wear resistant agent, PBT resin and reinforcing agent into three hoppers of a twin-screw extruder respectively, and control the discharge flow of the three hoppers, and then perform melt extrusion granulation. After extrusion granulation by the twin-screw extruder, dry at 110°C for 4 hours to obtain PBT composite particles, wherein the parameter setting of the twin-screw extruder is the same as that in Example 1.

[0093] Comparative Example 4

[0094] This comparative example provides a PBT composite material, wherein the raw materials of the PBT composite material include, by weight: 45 parts of PBT resin, 25 parts of reinforcing agent, 12 parts of organic phosphorus flame retardant, 6 parts of nitrogen flame retardant, 1 part of anti-wear agent, and 4 parts of lubricant. The specific types of raw materials are the same as those in Example 1.

[0095] Based on the raw material composition of the above-mentioned PBT composite material, this comparative example also provides a method for preparing the PBT composite material, comprising the following steps:

[0096] S11, adding the anti-wear agent and the lubricant to anhydrous ethanol, and using a magnetic stirrer to disperse and stir for 5 minutes to obtain a uniformly mixed mixture;

[0097] S21, adding the organic phosphorus flame retardant and the nitrogen flame retardant to the mixed solution in batches, using a magnetic stirrer to disperse and stir for 5 minutes, and then putting it into a vacuum drying oven to remove ethanol to obtain a uniformly mixed flame retardant and wear-resistant agent;

[0098] S31. Add the flame retardant and wear resistant agent, PBT resin and reinforcing agent into three hoppers of a twin-screw extruder respectively, and control the discharge flow of the three hoppers, and then perform melt extrusion granulation. After extrusion granulation by the twin-screw extruder, dry at 110°C for 4 hours to obtain PBT composite particles, wherein the parameter setting of the twin-screw extruder is the same as that in Example 1.

[0099] Comparative Example 5

[0100] This comparative example provides a PBT composite material, wherein the raw materials of the PBT composite material include, by weight: 45 parts of PBT resin, 25 parts of reinforcing agent, 12 parts of organic phosphorus flame retardant, 6 parts of nitrogen flame retardant, 1 part of anti-wear agent, 1 part of antioxidant, and 3 parts of lubricant. The specific types of the raw materials are the same as those in Example 1.

[0101] Based on the raw material composition of the above-mentioned PBT composite material, this comparative example also provides a method for preparing the PBT composite material, comprising the following steps:

[0102] S11, adding the anti-wear agent, antioxidant, lubricant, organophosphorus flame retardant and nitrogen flame retardant to anhydrous ethanol, using a magnetic stirrer to disperse and stir for 5 minutes, and then putting it into a vacuum drying oven to remove ethanol to obtain a uniformly mixed flame retardant and wear-resistant agent;

[0103] S21. Add the flame retardant and wear resistant agent, PBT resin and reinforcing agent into three hoppers of a twin-screw extruder respectively, and control the discharge flow of the three hoppers, and then perform melt extrusion granulation. After extrusion granulation by the twin-screw extruder, dry at 110° C. for 4 hours to obtain PBT composite particles, wherein the parameter setting of the twin-screw extruder is the same as that in Example 1.

[0104] The properties of the PBT composite particles obtained in Examples 1 to 3 and Comparative Examples 1 to 5 were measured, and the results are shown in Table 1. At the same time, the antioxidant properties (performance after aging) of the PBT composite particles obtained in Examples 1 to 3 and Comparative Examples 1 to 5 were tested according to the method of national standard GB / T 2423.50 (temperature: 85°C; humidity: 85% RH; aging time 1000h), and the results are shown in Table 2.

[0105] Table 1 Properties of PBT composite particles obtained in Examples 1 to 3 and Comparative Examples 1 to 5

[0106]

[0107]

[0108] Table 2 Antioxidant properties of PBT composite particles obtained in Examples 1 to 3 and Comparative Examples 1 to 5

[0109]

[0110] It should be noted that UL94 standard UL94 is a flammable material test standard developed by the Underwriters Laboratories of the United States. This standard is mainly used to evaluate the spontaneous combustion and combustion performance of plastic materials. Its test methods include horizontal combustion test and vertical combustion test. GWIT is the glow wire ignition temperature.

[0111] As can be seen from Table 1, Comparative Example 1 does not contain an anti-wear agent, but the flame retardant performance is worse than that of Example 1, thereby indicating the synergistic flame retardant effect of the flame retardant and the anti-wear agent. Comparative Example 2 does not contain a phosphorus-based flame retardant, and Comparative Example 3 does not contain a nitrogen-based flame retardant, but the flame retardant performance is worse than that of Example 1, indicating that the nitrogen-based flame retardant and the phosphorus flame retardant have a synergistic flame retardant effect. Comparative Example 4 does not contain an antioxidant, but the wear resistance is worse than that of Example 1, indicating the synergistic effect of the antioxidant and the lubricant. Comparative Example 5 does not add an ethanol mixing step, and the particles are added directly, and can be added as needed, but the performance is worse than that of Example 1, indicating that the raw materials need to be mixed in the manner of the example. As can be seen from Table 2, the performance of the PBT composite particles after aging changes little.

[0112] In addition, one or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:

[0113] In the embodiment of the present invention, based on the combination of specific flame retardant modifiers, wear resistant agents, antioxidants and lubricants, the halogen flame retardant in the product can achieve high CTI and excellent mechanical properties while exerting flame retardant properties, and the added halogen-free flame retardant and other additives can not only achieve extremely high glow wire ignition temperature, but also take into account wear resistance and antioxidant properties. At the same time, the compatibility of each added component with the PBT matrix resin is significantly improved. The product has high impact resistance, high fluidity and strong processability.

[0114] In the embodiment of the present invention, glass fiber, nitrogen flame retardant, phosphorus flame retardant and wear-resistant additive are added and compounded, and the nitrogen flame retardant, phosphorus flame retardant and wear-resistant additive are evenly mixed, which can significantly improve the wear resistance of the PBT composition, while ensuring the impact resistance and flame retardancy of the PBT composition. And when adding, the flame retardant is fully mixed, so that the long-term compatibility of the flame retardant and PBT is good, and the long-term flame retardancy is improved.

[0115] In the embodiment of the present invention, a specific ratio is used to ensure that the material has high mechanical properties while achieving ideal flame retardant properties, and the wear resistance can meet the needs of complex working environments.

[0116] In the embodiment of the present invention, the PBT composite material meets the following properties: tensile strength of 90MPa to 130MPa, flame retardancy of 1.6mm is V0, glow-wire ignition temperature is greater than 700°C, friction coefficient is 0.2 to 0.3, and performance changes are small after aging.

[0117] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A PBT composite material, characterized in that: In parts by weight, the raw materials of the PBT composite material include: 35 to 45 parts of PBT resin, 12 to 35 parts of reinforcing agent, 10 to 35 parts of halogen-free flame retardant, 1 to 5 parts of wear-resistant agent, 0.1 to 1 part of antioxidant, and 0.2 to 3 parts of lubricant, wherein the halogen-free flame retardant is composed of organic phosphorus flame retardant and nitrogen flame retardant.

2. The PBT composite material according to claim 1, characterized in that: The mass ratio of the organic phosphorus flame retardant to the nitrogen flame retardant is (8-25):(2-10).

3. The PBT composite material according to claim 1, characterized in that: The halogen-free flame retardant includes one or more of red phosphorus, aluminum hypophosphite, ammonium polyphosphate, diethyl aluminum hypophosphite, melamine, aminotrimethylene phosphonic acid aluminum, diethyl aluminum phosphate, melamine cyanurate, melamine phosphate, phenyl phosphate, siloxane and 2,6-diformyl-4-methoxyphenol.

4. The PBT composite material according to claim 1, characterized in that: The reinforcing agent is short fibers, the size of the short fibers is 1 mm to 5 mm, and the short fibers include: one or more of carbon fibers, glass fibers and basalt fibers.

5. The PBT composite material according to claim 1, characterized in that: The wear-resistant agent includes: one or more of carbon nanotubes, expandable graphite, graphene, graphene oxide and carbon fiber.

6. The PBT composite material according to claim 1, characterized in that: The antioxidant includes: one or more of bis(4-octylphenol) diphosphate, tris(2,4 di-tert-butyl) phosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and phosphite antioxidants; and / or, the lubricant includes: ethylene bisstearamide.

7. The PBT composite material according to claim 1, characterized in that: The PBT composite material meets at least one of the following properties: tensile strength of 90MPa to 130MPa, flame retardancy of 1.6mm at V0, glow-wire ignition temperature of more than 700°C, and friction coefficient of 0.2 to 0.

3.

8. A method for preparing the PBT composite material according to any one of claims 1 to 7, characterized in that: The method comprises: Adding an anti-wear agent, an antioxidant and a lubricant into a solvent, and then mixing them to obtain a mixed solution; Adding halogen-free flame retardant to the mixed solution in batches, stirring and drying, and obtaining a flame retardant and wear-resistant agent; The flame retardant and wear resistant agent, PBT resin and reinforcing agent are respectively added into three hoppers of a twin-screw extruder, and the material discharge flow rates of the three hoppers are controlled, followed by melt extrusion granulation and drying to obtain a PBT composite material.

9. The method according to claim 8, characterized in that The temperature of the twin-screw extruder is 100° C. to 300° C., and the screw speed is 150 r / min to 250 r / min.

10. The method according to claim 8, characterized in that The discharge flow rates of the three hoppers are 20kg / h to 30kg / h, 4kg / h to 10kg / h and 0.5kg / h to 5kg / h respectively.

Citation Information

Cited By

  • Flame-retardant additive, polyester resin composition containing flame-retardant additive and application of polyester resin composition

    CN120590687A

  • A flame retardant additive, a polyester resin composition comprising the same, and applications thereof

    CN120590687B